Students’ Perceptions of the Effectiveness of the Methods Used to Enhance Discipline in Public Secondary Schools in Nyahururu Division, Laikipia West District, Kenya - Kaguamba, Grace N.; Muola, James Muthee (International Association of African Researchers, 2010)
Many methods are used to enhance discipline in secondary schools. Among them are corporal punishment, guidance and counselling, psychological punishment and suspension from school. The use of corporal punishment was banned by the government and teachers were expected to use alternative methods. The opinion of the students on this matter was not sought. The main purpose of this study was to investigate students’ perception of the effectiveness of the methods used to enhance discipline in public schools in Nyahururu division of Laikipia West District. The descriptive survey method was used. From a population of 2497 students, a sample of 333 was selected using the proportionate, stratified and simple random sampling methods. Data was collected using a self-administered student questionnaire developed by the researchers. Descriptive statistics were used to analyse the data. The results showed that students perceived guidance and counselling as more effective in enhancing discipline than other methods. The study also revealed that factors such as age, grade and type of school affected students’ perception of the effectiveness of the various methods. From the study it was recommended that a good student-teacher relationship be cultivated in schools and guidance and counselling be enhanced.
Keywords: Perception; Discipline; Secondary school; Grade